Cytogenetic identification of wheat-Psathyrostachys huashanica amphiploid × triticale progenies for English grain aphid resistance (Scientia Agricola, 2013)
English grain aphid (EGA, Sitobion avenae Fabricius) is an important pest in wheat (Triticum aestivum L.). To develop EGA-resistant varieties, introducing the desirable genes from related species is regarded as an efficient avenue. In this study, the F1, F2 and F3 plants derived from the cross of EGA-susceptible wheat-Psathyrostachys huashanica Keng ex Kuo amphiploid (PHW-SA, AABBDDNsNs) and EGA-resistant triticale (Zhongsi 828, AABBRR) were analyzed for EGA resistance. Consequently, PHW-SA was moderately susceptible while Zhongsi 828 and their F1 hybrids were immune, suggesting that the resistance is dominant. All the F2 plants showed high resistance or immunity over two years, indicating that EGA resistance genes are more likely carried by the rye (Secale cereale L.) chromosomes rather than the genomes A or B of Zhongsi 828. In the F3 generation, 25 of 239 lines became susceptible. Giemsa C-banding patterns revealed that these F3 lines had 38-40 chromosomes, including complete rye genome except 5R (and 2R in five lines). Genomic in situ hybridization analysis confirmed this result. During meiosis, all the chromosomes formed bivalents. Six bivalents in 20 lines and five bivalents in five lines were characterized from rye. In contrast, their F2 parental lines had 42 chromosomes (21 bivalents), containing 1R-7R of rye. No P. huashanica chromosomes were detected. Therefore, we propose that the rye chromosome 5R may be related to EGA resistance.